A new uniqueness theorem of wave profiles for a 2-D bistable lattice dynamical system. (May 2021) - Lan, Shuangting; Weng, Peixuan; Xu, Zhaoquan
Abstract: The wave propagation dynamics of bistable lattice dynamical systems was extensively studied in literatures. It is a challenging problem if the wave profiles are unique up to translation. In this note, we establish a new uniqueness theorem of wave profiles for a 2-D bistable lattice dynamical system with global interaction. The obtained result greatly extends the known results in the literature, which need the monotonicity and smoothness restrictions on the wave profiles.